2001
DOI: 10.1053/jhep.2001.27810
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cell-mediated uptake of a hepatitis B virus: A new concept of liver targeting of hepatotropic microorganisms

Abstract: The liver is a target for many infectious agents, most notably hepatitis viruses. However, several receptor molecules identified so far for hepatitis viruses were found to be ubiquitously expressed and can thus not account for efficient liver targeting. Using a model hepatitis B virus, the duck hepatitis B virus (DHBV), we have obtained data indicating that scavenging liver sinusoidal endothelial cells (LSEC), rather than hepatocytes themselves, play the key role in the initial uptake of viral pathogens into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
94
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(94 citation statements)
references
References 30 publications
0
94
0
Order By: Relevance
“…Recent work suggests that DHBV is internalized by receptormediated endocytosis (10)(11)(12)18). Based on these data we hypothesized that TLM deficiency might result in retention of the virus within the endosomal compartment.…”
Section: Tlm Integrity Is Essential For Dhbv To Escape From the Endosmentioning
confidence: 88%
See 1 more Smart Citation
“…Recent work suggests that DHBV is internalized by receptormediated endocytosis (10)(11)(12)18). Based on these data we hypothesized that TLM deficiency might result in retention of the virus within the endosomal compartment.…”
Section: Tlm Integrity Is Essential For Dhbv To Escape From the Endosmentioning
confidence: 88%
“…Published work suggested that hepadnaviral infection relies on an endocytic process (10)(11)(12)18), and the presence of enveloped viral particles in purified endosomal fractions at an early stage of infection was very recently visualized by electron microscopy (unpublished data). However, the mechanisms allowing escape of the virus and the viral nucleocapsid from the endocytotic 3, 5, and 7).…”
Section: Discussionmentioning
confidence: 99%
“…Receptor-mediated transcytosis of HBV results in efficient delivery of virus from the circulation to the target cell population (23,25) but the identity of the transcytosing receptor has not been determined. If operative in the setting of natural infection, this process could facilitate the establishment of initial as well as chronic infection.…”
Section: Discussionmentioning
confidence: 99%
“…In search for a possible entry pathway of DHBV into hepatocytes, it was postulated that DHBV needs to be transported across LSECs to reach the hepatocyte compartment in the liver and that this pathway is conserved in vitro (Breiner et al, 2001). By co-staining with fluorescently labelled acLDL, we found DHBe but not DHBs from SVPs associated with LSECs.…”
Section: Discussionmentioning
confidence: 77%
“…Thus, another receptor or additional factors are required for DHBV infection. Also, the participation of another cell type, LSECs, which are in close contact with hepatocytes in vivo, has been discussed previously (Breiner et al, 2001). The observation that DHBe inhibited DHBV infection prompted us to find out which cells were able to bind or take up DHBe.…”
Section: Association Of Dhbe With Pdlc Subpopulationsmentioning
confidence: 92%